2021
DOI: 10.1136/ijgc-2021-002587
|View full text |Cite
|
Sign up to set email alerts
|

Radical hysterectomy in early cervical cancer in Europe: characteristics, outcomes and evaluation of ESGO quality indicators

Abstract: IntroductionComprehensive updated information on cervical cancer surgical treatment in Europe is scarce.ObjectiveTo evaluate baseline characteristics of women with early cervical cancer and to analyze the outcomes of the ESGO quality indicators after radical hysterectomy in the SUCCOR database.MethodsThe SUCCOR database consisted of 1272 patients who underwent radical hysterectomy for stage IB1 cervical cancer (FIGO 2009) between January 2013 and December 2014. After exclusion criteria, the final sample includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The inclusion criteria were 15 : age ≥18 years; histologic type: squamous cell carcinoma, adenocarcinoma, or adenosquamous carcinoma; and pelvic magnetic resonance image (MRI) confirming a tumor diameter ≤4 cm with no parametrial invasion and a preoperative computerised tomography (CT) scan, MRI, or positron emission tomography-computed tomography (PET-CT) demonstrating no extracervical metastatic disease. The operative report had to describe type B-C radical hysterectomy with bilateral pelvic lymphadenectomy by either minimally invasive surgery (laparoscopic or robotic) or open surgery, including at least 10 pelvic nodes.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The inclusion criteria were 15 : age ≥18 years; histologic type: squamous cell carcinoma, adenocarcinoma, or adenosquamous carcinoma; and pelvic magnetic resonance image (MRI) confirming a tumor diameter ≤4 cm with no parametrial invasion and a preoperative computerised tomography (CT) scan, MRI, or positron emission tomography-computed tomography (PET-CT) demonstrating no extracervical metastatic disease. The operative report had to describe type B-C radical hysterectomy with bilateral pelvic lymphadenectomy by either minimally invasive surgery (laparoscopic or robotic) or open surgery, including at least 10 pelvic nodes.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The estimated number of new cases of cervical cancer in Europe in 2020 was 58 169, with 25 989 deaths 1. Surgery represents the main treatment in early stages (International Federation of Gynecology and Obstetrics (FIGO) 2018 IA–IB2) and the 5-year disease-free survival rate in the largest European cohorts ranges from 87.7% to 88.3% 2 3. However, several differences in survival can be found across Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, secondary endpoint analyses demonstrated that MIS showed similar perioperative outcomes with open approach, and did not improve postoperative quality of life [ 19 , 20 ]. Thus, updated guidelines including the NCCN and ESGO support that laparotomy should be preferred procedure for radical hysterectomy [ 4 , 21 ].…”
Section: Discussionmentioning
confidence: 99%